Penguatan Peran Sosial dan Keagamaan Melalui Kegiatan TPA dan Pengajian di Ranting Aisyiyah Pra Kartasura: Strengthening Social and Religious Roles Through TPA Activities and Recitation in the Aisyiyah Pra Kartasura Branch - Nurvita Septiayu Putri Widyanti; Desi Saraswati; Rizma Nadia Putri; Nova Artha Mevia; Nabila Tarivita Putri; Alvira Choirunissa Putri; Anggita Putri Pramesti; Zahra Raudhotul Janah; Ahmad Nurrohim (Litera Academica Publishing, 2025)
Social changes and technological developments in the era of globalization have an impact on decreasing community participation in religious activities. The main focus of this research is to analyze the contribution of Al-Qur'an Education Park (TPA) activities and mother's recitations organized by the Kartasura Branch of 'Aisyiyah (PRA) in strengthening the social and religious role of the community. Using a qualitative descriptive approach with a case study method, data was collected through participant observation, interviews and documentation. The results show that TPA activities form a culture of learning the Koran from an early age and improve children's religious character, while routine recitation strengthens Islamic brotherhood, Islamic literacy, and the strategic role of women in the family and society. This activity also succeeded in reviving the function of the mosque as a center for da'wah and empowerment. This program has proven to be able to increase congregational participation and provide significant social and spiritual impacts for the local community. This research contributes to the development of a mosque-based community empowerment model that is integrative, adaptive and sustainable in facing the progress of the times.